Analisis Kualitas Sistem Informasi Dalam Pelayanan Publik Di Kantor Bursa Efek Indonesia Cabang Medan - Nurjannah, Nurjannah; Zahru Saritza; Faizah Khairani Srg; Irvan Affandi; Farhan, Farhan; Muhammad Ikrom Nst; Shintami Oktavia (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study aims to analyze the quality of information systems used in public services at the Medan Branch Of ice of the Indonesia Stock Exchange (BEI). The quality of information systems plays an important role in improving efficiency, effectiveness, and user satisfaction, especially in a public service environment that demands transparency and accuracy of information. This study uses a quantitative descriptive approach with data collection through questionnaires distributed to employees, investors, and the general public as service users at the Medan IDX. The main focus of this study is to evaluate three main aspects of information system quality, namely system quality (reliability, ease of use, and accessibility), information quality (accuracy, relevance, and speed of delivery), and service quality (responsiveness, technical support, and professionalism). The results show that most users are satisfied with the quality of the existing information system, although there are some shortcomings that need to be corrected, such as slow response times during peak hours and the need for system updates that are more adaptive to technological developments. The implications of this study provide strategic recommendations to improve the quality of information systems, including training for service of icers, investment in more sophisticated technological infrastructure, and the implementation of a periodic evaluation mechanism for the system used. With these improvements, it is expected that the Indonesia Stock Exchange Medan Branch can provide more optimal public services, strengthen investor confidence, and support the growth of the capital market in Indonesia)